Students' mathematical lateral thinking skills in creative problem-solving - Yusmin, Edy; Yani T, Ahmad; Pasaribu, Revi Lestari; Fitriawan, Dona (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
This study aimed to examine students' mathematical lateral thinking skills in creative problem-solving, differences in subjects' answers based on the level of their study period, and factors that affect students' lateral thinking skills. The descriptive method was used in the form of an educational survey. The sampling technique used in this research was stratified random sampling. The research subjects were first, third, and fifth-semester students of Mathematics Education at FKIP Tanjungpura University in 2019. The data collection technique used was the